Pengaruh Audit Tenure, Ukuran Kap, Dan Spesialisasi Audi-tor Terhadap Ketepatan Waktu Pelaporan Keuangan - Atika, Safira Nur; Baridwan, Zaki (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to determine the effect of audit tenure, Public Accounting Firm size, and auditor specialization on the timeliness of financial reporting of 492 manufacturing companies listed on the Indonesia Stock Exchange between 2019 and 2021. The data includes the companies’ financial statements collected through documentation from the IDX official website. The samples are selected through purposive sampling method, and are analyzed by multiple regression utilizing SPSS 24 software. The results revealed that audit tenure had a negative effect on the timeliness of financial reporting. Whilst, Public Accounting Firm size and auditor specialization had a positive effect on the timeliness of financial reporting.